2023
DOI: 10.5194/acp-23-15711-2023
|View full text |Cite
|
Sign up to set email alerts
|

Role of thermodynamic and turbulence processes on the fog life cycle during SOFOG3D experiment

Cheikh Dione,
Martial Haeffelin,
Frédéric Burnet
et al.

Abstract: Abstract. In this study, we use a synergy of in situ and remote sensing measurements collected during the SOuthwest FOGs 3D experiment for processes study (SOFOG3D) field campaign in autumn and winter 2019–2020 to analyse the thermodynamic and turbulent processes related to fog formation, evolution, and dissipation across southwestern France. Based on a unique measurement dataset (synergy of cloud radar, microwave radiometer, wind lidar, and weather station data) combined with a fog conceptual model, an analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 63 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…But Dione et al (2023) found much larger values (0.01 < σ 2 w < 0.04 m 2 .s −2 ) during the stable/adiabatic transition of the 4 deepest fog events of SOFOG3D and an increase in TKE of up to 0.4 m 2 .s −2 . These discrepancies may be explained by the contrasting environment between the two measurement areas (Thornton et al, 2023).…”
Section: Determination Of the Thin-to-thick Transition Timementioning
confidence: 80%
See 3 more Smart Citations
“…But Dione et al (2023) found much larger values (0.01 < σ 2 w < 0.04 m 2 .s −2 ) during the stable/adiabatic transition of the 4 deepest fog events of SOFOG3D and an increase in TKE of up to 0.4 m 2 .s −2 . These discrepancies may be explained by the contrasting environment between the two measurement areas (Thornton et al, 2023).…”
Section: Determination Of the Thin-to-thick Transition Timementioning
confidence: 80%
“…They found that α closure eq depends mainly on the CTH and pointed out that thinner fog with LWP values lower than 20 g.m −2 has α eq values below 0.6 and can even reach negative values. Dione et al (2023) used this model to analyze the four deepest fogs of SOFOG3D and revealed that α closure eq increases from 0 to 0.5 during the thin-to-thick transition and reaches 0.5 when LWP > 20 g.m −2 . We now use the CDP measurements to analyze fog adiabaticity derived from in situ measurements.…”
Section: Equivalent Adiabaticity From Closurementioning
confidence: 99%
See 2 more Smart Citations
“…Similar environmental features to those found to influence the mean daily FLS occurrence in Pauli et al (2020) are used, specifically air temperature (t2m) and specific humidity (q) at 2 m, wind speed (ws) at 10 m, and mean surface pressure (msp). While the FLS life cycle is also influenced by large-scale dynamic and thermodynamic conditions (Andersen et al, 2020;Dione et al, 2023), in this study we focus on the relationships of the FLS life cycle to environmental conditions near the ground and at the local scale. The ERA5 data set is rescaled to the spatial resolution of the FLS data set using nearest-neighbour interpolation.…”
Section: Reanalysis Data Setmentioning
confidence: 99%